2015
DOI: 10.1080/09603123.2015.1119807
|View full text |Cite
|
Sign up to set email alerts
|

Control beliefs and engagement in hygienic and safety behaviours: the case of foodborne illness

Abstract: Foodborne illness is an ever-growing concern in public health. Studies found that conventional training is not enough to cause employees to apply the hygiene and safety measures. The present study explores control and fatalistic beliefs as potential factors for explaining engagement in preventive actions. Two-hundred and seventeen employees of a fast-food restaurant (75 % of all staff) answered a questionnaire assessing their control beliefs, fatalistic beliefs, risk perception, and engagement in hygienic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
(84 reference statements)
1
3
0
3
Order By: Relevance
“…These study results support the findings of other site-specific research of community gardeners, which concluded that soil testing challenges were related to perceived behavioral control challenges such as paucity of training, insufficient financial support, and difficulty interpreting results [13,27,30,32]. Similar to other studies of food safety and protective behaviors, targeting PBC, particularly related to self-efficacy in interventions may help to increase behavioral compliance [53,54,55]. Moreover, studies recommend that high PBC to perform a behavior occurs when people: (1) believe they can perform the behavior; (2) possess the resources to conduct the behavior; and (3) are able to overcome or manage barriers to the behavior [35,56].…”
Section: Discussionsupporting
confidence: 86%
“…These study results support the findings of other site-specific research of community gardeners, which concluded that soil testing challenges were related to perceived behavioral control challenges such as paucity of training, insufficient financial support, and difficulty interpreting results [13,27,30,32]. Similar to other studies of food safety and protective behaviors, targeting PBC, particularly related to self-efficacy in interventions may help to increase behavioral compliance [53,54,55]. Moreover, studies recommend that high PBC to perform a behavior occurs when people: (1) believe they can perform the behavior; (2) possess the resources to conduct the behavior; and (3) are able to overcome or manage barriers to the behavior [35,56].…”
Section: Discussionsupporting
confidence: 86%
“…When they are corrected, individuals adopt a more appropriate behavior (Weiner, Osborne, & Rudolph, 2011;Kouabenan & Ngueutsa, 2015). Correcting erroneous beliefs is in fact already used in cognitive therapy as a strategy to treat problem gambling (Ladouceur & Walker, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a different context regarding the frequent food-handlers in Australia, the positive impact of PBC was found on the behavior of keeping food at the correct temperature (Mullan et al, 2015). Similarly, the degree of hygienic and safety implementation was found correlated with handlers' perception of the capability of implementing them in the case of food-handlers of fast-food restaurants in France (Kouabenan & Ngueutsa, 2016). The discrepancy of impacts between models may relate to the difference in at-home food processing culture and habits.…”
Section: Discussionmentioning
confidence: 92%